Reversal of Indices in Infinite Triangular Sums

We have:

\sum_{i=0}^{\infty} \sum_{j=i}^{\infty} \varphi(i,j) = \sum_{j=0}^{\infty} \sum_{i=0}^{j} \varphi(i,j)

because

\sum_{i=0}^{\infty} \sum_{j=i}^{\infty} \varphi(i,j) = \sum_{\begin{array}{c}i,j \\ 0 \le i \le j < \infty\end{array}} \varphi(i,j) = \sum_{j=0}^{\infty} \sum_{i=0}^{j} \varphi(i,j)

In an earlier post, I showed the finite version of this result:

\sum_{i=0}^{n} \sum_{j=i}^{n} \varphi(i,j) = \sum_{j=0}^{n} \sum_{i=0}^{j} \varphi(i,j)

This might be seen to hold as both sums are

\sum_{\begin{array}{c}i,j \\ 0 \le i \le j \le n\end{array}} \varphi(i,j)

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s


%d bloggers like this: